Development of Technology and Information based Supervision Applications to Improve the Performance of PJOK Teachers - Ardhi, Ardhi Surya Wijaya; Indra Kasih; Budi Valianto (UNIB Press, 2024)
Subdistrict, Serdang Bedagai RegencyThe type of research in this study is qualitative research development studies used in a study must be based on the problems raised. Research and development in this process Using a quantitative approach and using Research and Development research design This development research aims to produce an application product that can streamline the task of the principal in supervising while improving the performance of physical education teachers. The application developed is based on technology and information so that it is easy to use for supervisors in this case is the principal. This application product is suitable for use based on validation by supervision experts, technology and information experts, application design experts, trial results and respondent response results. Application product development research makes the principal's duties in the field of supervision more effective and efficient so that the principal as a supervisor is able to carry out his duties optimally.